Effects of Angiogenic Factors on the Epithelial-to-Mesenchymal Transition and Their Impact on the Onset and Progression of Oral Squamous Cell Carcinoma: An Overview - Silvia Pomella; Ombretta Melaiu; Maria Dri; Mirko Martelli; Marco Gargari; Giovanni Barillari (Cells, 2024)
High levels of vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF)-2 and angiopoietin (ANG)-2 are found in tissues from oral squamous cell carcinoma (OSCC) and oral potentially malignant disorders (OPMDs). As might be expected, VEGF, FGF-2, and ANG-2 overexpression parallels the development of new blood and lymphatic vessels that nourish the growing OPMDs or OSCCs and provide the latter with metastatic routes. Notably, VEGF, FGF-2, and ANG-2 are also linked to the epithelial-to-mesenchymal transition (EMT), a trans-differentiation process that respectively promotes or exasperates the invasiveness of normal and neoplastic oral epithelial cells. Here, we have summarized published work regarding the impact that the interplay among VEGF, FGF-2, ANG-2, vessel generation, and EMT has on oral carcinogenesis. Results from the reviewed studies indicate that VEGF, FGF-2, and ANG-2 spark either protein kinase B (AKT) or mitogen-activated protein kinases (MAPK), two signaling pathways that can promote both EMT and new vessels’ formation in OPMDs and OSCCs. Since EMT and vessel generation are key to the onset and progression of OSCC, as well as to its radio- and chemo-resistance, these data encourage including AKT or MAPK inhibitors and/or antiangiogenic drugs in the treatment of this malignancy.